Optimized Regional Development Planning for Samosir Tourism: Integrating Seasonal Accommodation Occupancy and Sustainable MSME Empowerment - Dina Rosari; Ngatemin Ngatemin; Dewi Yanti; Bejo Mulyadi (Jurnal Mamangan, 2026)
This study examines tourism seasonality's impact on accommodation occupancy and MSME performance in Samosir Regency, Lake Toba UNESCO Global Geopark, using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with a complete census of 80 stakeholders. Results confirm seasonality strongly predicts occupancy fluctuations (β=0.69, p<0.001, R²=0.48), while bidirectional occupancy-MSME linkages explain 41% of MSME revenue instability (β=0.46/0.31, p<0.001/0.002). Stakeholder integration emerges as the dominant driver of regional planning effectiveness (β=0.51, p<0.001), alongside occupancy (β=0.24) and MSME inputs (β=0.33), accounting for 63% of planning variance (SRMR=0.067). Findings provide an empirical framework for optimized planning, integrating seasonality mitigation, MSME empowerment, and inclusive governance to achieve sustainable tourism development in Indonesia's super-priority destinations.